Numerical Analysis on Spanwise Correlation of Vortex-Induced Force of Split Double-Box Beam - Lin Dong; Jie Jia; Lixin Zhang (Applied Sciences, 2022)
The vortex-induced force of bridges is not synchronized along the span direction. The spatial correlation of vortex-induced force becomes obvious when the span of the bridge structure gradually increases, and the mass gradually decreases. Therefore, it is important to study the spanwise correlation of vortex-induced forces of long-span bridges to ensure the accuracy of the prediction of vortex-induced vibration response of bridges. The study established and improved the theory and experimental research methods for vortex-induced vibration analysis of large-span bridges by discussing the spanwise correlation during vortex-induced vibration of the split double-box beam. Taking Xihoumen Bridge as the object, two-dimensional (2D) and three-dimensional (3D) numerical models of the scaled-down sections were designed and established based on the ANSYS Fluent platform and the RANS SST turbulence model. Based on the Newmark-β algorithm, a User Defined Function (UDF) was written for vortex vibration calculation, the three-dimensional bypass of the split double-box beam in static conditions and vortex-induced vibration of the split double-box beam of which were calculated, and the spanwise correlations of the aerodynamic coefficients, the surface pressure coefficients, and the wake wind velocity of the main girder section were analyzed for the static and vibration states of the bridge. The results show that the self-excited force of the split double-box beam in vortex-induced vibration improved its spanwise correlation. Compared with those in a static state, the spanwise correlation of the lift coefficient and torque coefficient increased by 55% and 87%, respectively, and the resistance coefficient increased by more than 10 times. The correlation of the pressure coefficients increased by 153%. The correlation of wake wind velocity increased by 37% in the along-wind direction and that in the across-wind and vertical-wind direction increased by more than 10 times. The accuracy of the numerical simulation results was verified by comparing the pressure distribution and pressure spanwise correlation of the main beam with field-measured data.